Klasifikasi Teks Pengaduan Suara Warga Kabupaten Pasuruan menggunakan Metode Maximum Entropy - Mayang Panca Rini; Putra Pandu Adikara; Sigit Adinugroho (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Suara Warga is a website that it provided by the government of Pasuruan Residence to receive complain from the society. In the application, the admin must pass on the complain to related official manually. To increase the efficient of time, it is needed a classification of the text, Maximum Entropy is a method that is used in this research with Confusion Matrix evaluation method which will count the evaluation from the equal-wont data and the unequal-wont data, with the complain as much 200 data. Before doing the classification, the first step which is done is pre-processing and the next is process of word quality. Classification is done through looking for the opportunity of every word in every document and the result of classification is got based on the higher opportunity result from document class. The result of equal-wont data evaluation produce better result than the result of the unequal-wont data evaluation with the accuration: 89,27%, precision: 92,49%, recall: 89,27% and f-measure: 89,44%.